A200 UNUSUAL PERIANAL MASS IN A CIRRHOTIC PATIENT: A CASE REPORT. (15th March 2019) - Masckauchan, M; Wong, P; Valenti, D
Abstract: Background: Patients with advanced cirrhosis and portal hypertension are at risk of developing portosystemic collaterals such as gastroesophageal varices, but these may also form in ectopic locations including the small intestine, colon, rectum, peritoneum and other intra-abdominal organs. Ectopic varices are at risk of bleeding, and up to 5% of all variceal hemorrhages originate from these ectopic sites. It is therefore important to familiarize oneself with their presentation and treatment options. Aims: Describe a case of rectal varices in a cirrhotic patient presenting with discomfort due to an unusual perianal mass. Methods: Case report and literature review. Results: A 61-year-old man presented to his routine hepatology follow-up with complaints of perianal pruritis and occasional mild hematochezia. Past medical history was significant for HIV, cirrhosis secondary to alcohol and hepatitis C infection successfully treated with direct-acting antivirals, previous esophageal variceal bleed and bipolar disorder. Physical exam revealed two large soft-tissue masses, one in the perianal region and the other in the left ischial region (Figure A). Laboratory investigations were non-contributory, while a flexible sigmoidoscopy demonstrated large rectal varices extending 20 cm into the rectum (Figure B). A doppler ultrasound confirmed the presence of complex venous structures within the perianal protrusion, consistent with external varices (Figure C). Indeed, the internal rectal varices had extended externally into the left ischial region as a soft-tissue mass. Insertion of a transjugular intrahepatic portosytemic shunt (TIPS) was performed but did not adequately reduce the size of the varices and was complicated by hepatic encephalopathy. Therefore, the patient was further treated with embolization of the superior hemorrhoidal arteries by interventional radiology. At follow-up, the rectal varices showed significant reduction in size (Figure D). Unfortunately, the patient died prior to subsequent endoscopic imaging and follow up. Conclusions: Diagnosis of ectopic varices is made with endoscopy and can be confirmed by color doppler ultrasound and contrast enhanced CT. Although no management guidelines are currently available, treatment options include endoscopic band ligation, endoscopic sclerotherapy, TIPS, percutaneous embolization or occlusion procedures such as balloon occluded retrograde transvenous obliteration (BRTO) by interventional radiology. Surgical interventions are usually of last resort given the high risk of death and complication rates in patients with advanced liver disease. Funding Agencies: None